Disentangling Electron Tunneling and Protein Dynamics of Cytochrome c Through a Rationally Designed Surface Mutation - Álvarez Paggi, Damián Jorge (2013)
Non-exponential distance-dependence of the apparent electron transfer (ET) rate has been reported for a variety of redox proteins immobilized on biocompatible electrodes, thus posing a physicochemical challenge of possible physiological relevance. We have recently proposed that this behaviour may arise from the structural and dynamical complexity not only of the redox proteins, but also from their interplay with strong electric fields present in the experimental setups and in vivo (J. Am Chem. Soc 2010, 132, 5769-5778). Therefore, protein dynamics are finely controlled by the energetics of both specific contacts and the interaction between the protein?s dipole moment and the interfacial electric fields. In turn, protein dynamics may govern electron transfer kinetics through reorientation from low to high donor-acceptor electronic coupling orientations. Here we present a combined computational and experimental study of WT cytochrome c and the surface mutant K87C adsorbed on electrodes coated with self assembled monolayers (SAMs) of varying thickness (i.e., variable strength of the interfacial electric field). Replacement of the positively charged K87 by a neutral amino acid allowed us to disentangle protein dynamics and electron tunnelling from the reaction kinetics and to rationalize the anomalous distance dependence in terms of (at least) two populations of distinct average electronic couplings. Thus, it was possible to recover the exponential distance dependence expected from ET theory. These results pave the way for gaining further insight into the parameters that control protein electron transfer.